Analisis Fungsi Jenis Pendidikan Bagi Anak Autis - Dwi Sari Usop (Anterior Jurnal, 2016)
Educate the children with autism are the same as educating the other children who attend regular schools. There are many variations of therapy, methods, strategies, techniques applied learning alternated with therapy, methods, strategies, and other learning techniques. This study is aims to determine the relationship between them and the functions of education provided. This study is a qualitative study based literature. The data collection is done by collecting documents such as books and research journals. Analysis of the data used was content analysis. The results showed that the relationship between the type of education is a mutually supportive relationship and can not be separated from one another. While the function of education for children with autism, there are three, namely: optimizing the function of sensory, communication and social interaction, and guided the ability and skills to take care of themselves.